Association between osteoporosis and mortality in Parkinson's disease with mediating effect of hip fractures: a Korean nationwide population-based study - Yeonju Jin; Bo Kyu Choi; Jong Woo Lee; Jin Yong Hong; Ickpyo Hong; Min Seok Baek; Min Seok Baek (Frontiers in Aging Neuroscience)
IntroductionThis study investigated the association between osteoporosis and mortality in patients with Parkinson's disease (PD) and the mediating role of hip fractures.MethodsA retrospective cohort study. Data were obtained from the 2009–2019 Korean National Health Insurance Service–National Sample Cohort databases. We extracted both the International Classification of Diseases, 10th Edition code (G20) and PD registration code (V124) to identify patients with PD. A Cox proportional hazards model was used to analyze the association between osteoporosis and mortality. Mediation analyses were performed to estimate the mediating effect of hip fracture between osteoporosis and mortality in patients with PD.ResultsOf the 2,084 patients with PD, 474 (18.5%) were diagnosed with osteoporosis, and 112 (4.4%) experienced hip fractures after PD diagnosis. In unadjusted mediation analysis, the direct effect of osteoporosis on mortality was not significant (β = 0.0309, 95%: confidence interval [CI] −0.0180–0.0798, p = 0.2149), whereas the indirect effect of hip fracture was (β = 0.0130, 95% CI 0.0048–0.0212, p = 0.0019). Similarly, in the adjusted model controlling for sex, age at diagnosis, and Charlson Comorbidity Index, the direct effect was not significant (β = 0.0011, 95% CI−0.0508–0.0529, p = 0.9675), whereas the indirect effect was (β = 0.0061, 95% CI 0.0009–0.0114, p = 0.0223).DiscussionThis study elucidated the association between osteoporosis and mortality in patients with PD by highlighting the mediating role of hip fractures. These findings thus underscore the importance of managing osteoporosis in patients with PD.